Tractography-Guided Deep Brain Stimulation of the Anteromedial Globus Pallidus Internus for Refractory Obsessive-Compulsive Disorder: Case Report. Issue 6 (17th July 2019) - Azriel, Amit; Farrand, Sarah; Di Biase, Maria; Zalesky, Andrew; Lui, Elaine; Desmond, Patricia; Evans, Andrew; Awad, Mohammed; Moscovici, Samuel; Velakoulis, Dennis; Bittar, Richard G
Abstract: BACKGROUND AND IMPORTANCE: Obsessive-compulsive disorder (OCD) is a disabling psychiatric disorder, mainly treated with psychotherapy and pharmacotherapy. Surgical intervention may be appropriate for patients with treatment-refractory OCD. Deep brain stimulation (DBS) is an alternative for previously common ablative surgical procedures. Tractography has been proposed as a method for individualizing DBS treatment and may have the potential to improve efficacy. CLINICAL PRESENTATION: We present a patient with treatment-refractory OCD previously treated with bilateral leucotomies, who underwent DBS surgery with targeting informed by tractography. Preoperative tractography to identify suitable DBS targets was undertaken. Structural images were also utilized for standard stereotactic surgical planning. The anteromedial globus pallidus internus (amGPi) was chosen as the target bilaterally after consideration of white matter projections to frontal cortical regions and neurosurgical approach. Bilateral amGPi DBS surgery was undertaken without adverse events. At 16-mo follow-up, there was a 48.5% reduction in OCD symptom severity as measured by the Yale-Brown Obsessive Compulsive Scale. CONCLUSION: The amGPi can be a successful DBS target for OCD. This is the first known case to report on DBS surgery postleucotomies for OCD and highlights the utility of tractography for surgical planning in OCD.